Resistência in vitro aos antimicrobianos e microbiota bucal e de leito ungueal de gatos diagnosticadas por sequenciamento genético em larga escala e espectrometria de massas - Portilho, Fábio Vinícius Ramos [UNESP] (2023)
The close contact between cats and humans increases the risk of transmission of pathogens through bites and scratches, due to the complexity of microorganisms in feline oral and nail microbiota. The present study investigated the microorganisms of bacterial and fungal origin in the oral cavity and claws of 100 apparently healthy cats using conventional and selective microbiological culture approaches, next-generation sequencing (NGS), and mass spectrometry (MALDI-TOF MS), as well as the in vitro susceptibility pattern of bacterial isolates to antimicrobials. In total, 671 bacteria and 33 yeasts were identified by MALDI-TOF MS. Neisseria animaloris (37/343=10.8%), Staphylococcus felis (29/343=8.5%), and Pasteurella multocida (24/343=7%) were the most prevalent bacteria in oral cavity samples (n=343), while the main yeast (n=19) was Candida albicans (13/19=68.4%). Staphylococcus pettenkoferi (44/328=13.4%), Staphylococcus felis (21/328=6.4%), and Staphylococcus simulans (19/328=5.8%) were the most frequent bacteria identified in claws samples (n=328), while Rhodotorula mucilaginosa (8/14=57.2%) was the most common yeast (n=14). NGS predominantly identified the genera Moraxella, Neisseria, Pasteurella, and Fusobacterium in oral cavity samples, and enterobacteria and staphylococci in nail bed samples, in addition to the less frequent identification of the genera Capnocytophaga and Bartonella, which have been identified in human infections. Levofloxacin, marbofloxacin, and amoxicillin/clavulanic acid were the most effective drugs against the main groups of bacteria identified. Multidrug resistance was observed in 17% (114/671) bacterial isolates, in addition to three staphylococci carrying the methicillin resistance gene (mecA). We highlight a high complexity of microorganisms in oral/claws microbiota of cats, the zoonotic risks of aggression caused by bites and scratches from domestic cats, as well as the high resistance of the isolates to conventional antimicrobials.